Compreensão psicodiagnóstica na contemporaneidade: diálogos com a fenomenologia e com Karl Jaspers - Nogueira, Guilherme (2021)
In practically all societies, past and present, people with dissonant behaviors from the majority come into focus, and psychopathology is one of the sciences that helps to reach the psychodiagnostic understanding of these people. A classic psychodiagnostic proposal is that of Karl Jaspers, who proposes to study what man experiences and how he does it, investigating together the patient's biography. For Jaspers to reach a scientific level, it was necessary to classify, define, differentiate and describe the particular psychic phenomena through the phenomenological method. Grouping and classifying symptoms is a process of great relevance for understanding society; thus, the objective of this research was to answer the problem: how is the diagnosis in mental health, through a critical understanding of phenomenology and the theory of Karl Jaspers? To answer this problem, phenomenology was presented as a research proposal and Karl Jaspers' model of psychopathology and psychodiagnosis, to investigate the position of the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5), of the biopsychosocial model of attention to mental health, dialoguing with phenomenology and Jaspers. This work was carried out through a theoretical research, based on the methodological development of the phenomenological method, and its theoretical foundation was carried out by the foundations of the phenomenological approach. According to the data collected, it is noted that Jaspers' proposal, by focusing on what the patient experiences and the meanings that this gives to their experience, has been maintained over more than one hundred years of its proposition, still managing to maintain it. updated and coherent for the clinical examination and humanized treatment of the patient, without the need to change objectives and methods throughout the author's new studies. The phenomenological posture allows respect for the experience lived by the service user, placing the professional and the patient in the relationship, for the understanding of the psychopathological experience. These postures are similar to the proposals of the biopsychosocial mental health care model, aimed at more humanized practices, which envision the patient as an active being in the process and the rescue of their dignity and emancipation. It is concluded that, even along the diagnostic path there have been many dehumanized postures, there has been, since the classics, a posture of humanization being rescued in contemporaneity, allowing dialogues between them to be made and, thus, there may be a foundation and possibilities of practices that value increasingly the person who experiences some mental disorder.